Performance Improvements in Conjugated Polymer Devices by Removal of Water‐Induced Traps. Issue 36 (18th July 2018) - Nikolka, Mark; Schweicher, Guillaume; Armitage, John; Nasrallah, Iyad; Jellett, Cameron; Guo, Zhijie; Hurhangee, Michael; Sadhanala, Aditya; McCulloch, Iain; Nielsen, Christian B.; Sirringhaus, Henning
Abstract: The exploration of a wide range of molecular structures has led to the development of high‐performance conjugated polymer semiconductors for flexible electronic applications including displays, sensors, and logic circuits. Nevertheless, many conjugated polymer field‐effect transistors (OFETs) exhibit nonideal device characteristics and device instabilities rendering them unfit for industrial applications. These often do not originate in the material's intrinsic molecular structure, but rather in external trap states caused by chemical impurities or environmental species such as water. Here, a highly efficient mechanism is demonstrated for the removal of water‐induced traps that are omnipresent in conjugated polymer devices even when processed in inert environments; the underlying mechanism is shown, by which small‐molecular additives with water‐binding nitrile groups or alternatively water–solvent azeotropes are capable of removing water‐induced traps leading to a significant improvement in OFET performance. It is also shown how certain polymer structures containing strong hydrogen accepting groups will suffer from poor performances due to their high susceptibility to interact with water molecules; this allows the design guidelines for a next generation of stable, high‐performing conjugated polymers to be set forth. Abstract : Removal of water‐induced traps that are omnipresent in conjugated polymer devices is demonstrated by a highly efficient mechanism. The underlying mechanism is shown, by which small‐molecular additives with water‐binding nitrile groups or alternatively water–solvent azeotropes are capable of completely removing water‐induced traps, leading to a significant improvement in performance of organic field‐effect transistors.